Harmonizing methods to assess the ecotoxicity of layered double hydroxides nanomaterials in a freshwater microalgae - Campos, Fábio André Marques de (2022)
Nanotechnology has experienced an unprecedent growth, marked by the development of innovative nanomaterials with unique physicochemical characteristics for a wide range of applications. Layered double hydroxides (LDH) are a great example of such innovation. Currently, risk assessment methodologies are based on test methods developed for conventional chemical’s characteristics and do not account for the specificities that nanomaterials exhibit. Under REACH (Registration, Evaluation, Authorisation and Restriction of Chemicals) and CLP (Classification, Labelling and Packaging of substances) EU regulations, nanomaterials are regarded as substances. The chemical safety assessment of nanomaterials is thus crucial to meet the needs for their registration and posterior commercialization. The safety assessment performed for REACH, based on the current non nano-specific ecotoxicological test methodologies might produce data with low relevance and reliability. Thus, the present study aimed to assess the impact of two different exposure methodologies, recommended by OECD (serial dilutions from a stock dispersion vs direct nanomaterial addition to each individual concentration), in the growth of the freshwater microalgae Raphidocelis subcapitata exposed to Zn-Al and Cu-Al LDHs. Moreover, different powder grain sizes (bulk, <25. 25-63, 63-125, 125- 250 and, >250 µm) of both LDHs were used for the exposure of the same microalgae regarding a possible grain size-dependent toxicity. Regarding exposure methodologies, differences were observed in the toxicity of Zn-Al LDH, however, there is no methodological difference in the toxicity output for Cu-Al LDH exposure. Zn-Al LDH toxicity was similar for all grain sizes, however, the 3 highest grain sizes of Cu-Al LDH produced lower toxicity when comparing to the bulk counterpart. Thus, a grain size separation for Cu-Al LDH might be of great advantage towards the formulation of an eco-friendlier nanomaterial. Exposure methodology results pose as a good starting point for ecotoxicological testing involving LDHs. Additionally, other studies with exposure methodologies and media, and different nanomaterials are needed, in order to achieve better standardization procedures for nano-specific test methodologies.